1978
DOI: 10.1136/gut.19.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Lower oesophageal sphincter response to gastrin--pharmacological or physiological?

Abstract: SUMMARY The response of the lower oesophageal sphincter (LOS) to intragastric instillation of protein was assessed in 10 healthy volunteers. Sphincter pressures were measured by a rapid pullthrough technique and serum gastrin concentrations during each test were determined by radioimmunoassay. Despite stimulation of gastrin release by protein instillation, no significant change in LOS pressure was observed. However, intravenous pentagastrin (0 25 and 0.5 jig/kg) produced an immediate increase in sphincter pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
1
5
0
Order By: Relevance
“…In contrast, the effect of sumatriptan 6 mg on lower oesophageal sphincter pressure was not maintained for nearly as long (≈ 1 h). A similar transient increase in lower oesophageal sphincter pressure has been noted in healthy subjects following, for example, pentagastrin 34 and gastrin 35 administration and could suggest that this short‐lived response is a characteristic of the lower oesophageal sphincter. Indeed, in vitro studies have suggested that the smooth muscle of the oesophageal body and lower oesophageal sphincter do possess different sensitivities to various compounds 36 .…”
Section: Discussionsupporting
confidence: 61%
“…In contrast, the effect of sumatriptan 6 mg on lower oesophageal sphincter pressure was not maintained for nearly as long (≈ 1 h). A similar transient increase in lower oesophageal sphincter pressure has been noted in healthy subjects following, for example, pentagastrin 34 and gastrin 35 administration and could suggest that this short‐lived response is a characteristic of the lower oesophageal sphincter. Indeed, in vitro studies have suggested that the smooth muscle of the oesophageal body and lower oesophageal sphincter do possess different sensitivities to various compounds 36 .…”
Section: Discussionsupporting
confidence: 61%
“…Therefore, neurotensin, or a neurotensin metabolite, might be responsible for the decrease in the LES pressure after a fatty meal. Several hormones released after food intake, such as gastrin, secretin, cholecystokinin, and glucagon, have been shown to influence the LES pressure (Nebel & Castell 1972, Giles et al 1969, Castell & Harris 1970, Cohen & Lipshutz 1971, Resin et al 1973, Jaffer et al 1974, but it has not been established whether these hormones are of any physiological importance in the regulation of the LES pressure (Grossman 1973, Cohen & Lipshutz 1974, Sturdevant 1974, Henderson et al 1978.…”
Section: Discussionmentioning
confidence: 99%
“…However, when endogenous gastrin release was stimulated by calcium gluconate, ZES patients showed increased LES pressure [63]. Besides ZES, previous studies revealed that a high dose of pentagastrin, a gastrin analog, increased LES pressure, but a low dose of gastrin did not [65][66][67]. Whereas gastrin-I (gastrin-17), one of the physiological gastrins, gives a conflicting result, Heil et al and Jennewein et al reported that a high dose of gastrin-17 induced an increased LES pressure, as did pentagastrin [68,69].…”
Section: Does Cure Of Infection Break the Gastroesophageal Reflux Barmentioning
confidence: 99%